PENGARUH MODEL PROJECT BASED LEARNING DAN LITERASI DIGITAL TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM DAN SOSIAL SISWA KELAS V SEKOLAH DASAR - Maman Rumanta; Rif’at Shafwatul Anam; Zaenusolihin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the influence of the Project Based Learning (PjBL) model and the lecture method, high and low levels of digital literacy, as well as the interaction between these factors on the learning outcomes of Science and Social Studies (IPAS) among fifth-grade students at SDN 01 Gunungsari, Banjarsari District, Lebak Regency. The research employed an experimental method by implementing two learning models, namely the Project Based Learning (PjBL) model and the lecture method, combined with students’ levels of digital literacy, categorized as high and low, to examine their effects on IPAS learning outcomes. After the learning process was completed, a learning achievement test was administered to measure the students’ academic performance. The research subjects were divided into two groups, namely the control group and the experimental group. The population consisted of all 60 fifth-grade students of SDN 01 Gunungsari, Banjarsari District, and the entire population was used as the research sample. The sample was divided into four groups: two groups served as the control group and two groups as the experimental group. The findings of the study indicated that:  there was a significant effect of the learning model on students’ learning outcomes, as shown by Fh = 6.830 and Sig. = 0.011 < 0.05; digital literacy had a significant positive effect on students’ learning outcomes, as shown by Fh = 6.601 and Sig. = 0.015 < 0.05; among students with high digital literacy, there was no significant difference in learning outcomes between those taught using the PjBL model and those taught using the lecture method, as indicated by th = 0.000 and Sig. = 1.000 > 0.05; among students with low digital literacy, there was a significant difference in learning outcomes between the two models, with students taught through PjBL achieving higher scores (27.80) compared to those taught through the lecture method (25.27), with t = 3.919 and p = 0.002; and  there was a significant interaction between the learning model and digital literacy affecting students’ learning outcomes, as shown by Fh = 6.830 and Sig. = 0.011 < 0.05. Based on these findings, it can be concluded that both the learning model and the level of digital literacy significantly influence students’ learning outcomes, and there is also a meaningful interaction between the two factors that collectively affect the learning outcomes of Science and Social Studies (IPAS) among fifth-grade students at SDN 01 Gunungsari, Banjarsari District, Lebak Regency.